A fungal‐based anthraquinone emodin for polylactide and polyethylene terephthalate in supercritical carbon dioxide (SC‐CO2) dyeing. Issue 3 (2nd February 2021) - Räisänen, Riikka; Montero, Gerardo A.; Freeman, Harold S.
Abstract: Bio‐based materials and new dyeing technologies have gained growing interest, as companies actively want to enhance their products sustainability and remove environmental and hazardous pollutants. This article describes for the first time waterless dyeing studies using supercritical carbon dioxide (SC‐CO2 ) and a natural anthraquinone dye emodin for polylactide (PLA) and polyester (PET) fabric colouration. The colour of the dyed materials was measured as CIELab values, and the K / S (λmax, abs ) value was reported. Colour fastness to rubbing and light was studied according to the relevant ISO standards. The results show that the small size and hydrophobic nature of the anthraquinone dye resulted in a uniform dyeing on PLA and PET fabrics with SC‐CO2 dyeing medium. The excellent rubbing fastness, and microscopic evaluation revealed that the dye had penetrated into the fiber structure completely. Also the light fastness properties were exceptionally high for natural dyes. Increased usage of biodegradable and recycled materials in textiles would benefit from biocolourants which are stable under end‐use conditions, produce bright colours and have acceptable tinctorial strength.